Generation of femtosecond polygonal optical vortices from a mode-locked quasi-frequency-degenerate laser - Hongyu Liu; Lisong Yan; Liang Wang; Dongfang Li; Shenao Zhang; Xin Liu; Heyan Liu; Kunjian Dai; Qing Wang; Jinwei Zhang (Light: Science & Applications, 2025)
Abstract Polygonal optical vortices—a new subset of optical vortices—uniquely enable numerous applications due to the new degrees of freedom offered and their customizable light intensity structure. So far, their generation has only been reported for continuous wave. Here, we demonstrate the first femtosecond polygonal optical vortex pulses, which is also the first pulsed demonstration of such vortices in general. From a mode-locked Yb:KGW laser oscillator, femtosecond Hermit-Gaussian pulses at the quasi-frequency-degenerate state were generated and subsequently converted by astigmatic mode conversion to femtosecond polygonal optical vortices. They have light intensity distributions of square, pentagonal, and hexagonal shapes and carry orbital angular momentums. In all these variations, the average power and pulse duration are greater than one watt and less than 500 fs. These results open the way to new applications in the fields of femtosecond optical tweezer and three-dimensional microstructure fabrication.